Uptake of triphenylmethane and cellular localization of enzyme for its decolorization in enterobacter cloacae MG82 - Jeong, M.-S.; Kwak, S.-J.; Kim, B.-H.; Chung, Y.-G.; Kang, S.-O.; Min, K.-H. (1997)
Triphenylmethane was decolorized rapidly by Enterbacter cloacae MG 82 at initial reaction time. The spheroplast showed higher activity of tripheriylmethane decolorization than that of intact cell suspension. The outer part of the bacterial cell envelope and the peptidoglycan are important for the function of transport barrier of triphenylmethane. In intact cell, decolorization activity was higher at 37°c than at 0°C, indicating that triphenylmethane decolorization is due to the enzyme reaction. Culture filtrate showed no decolorization activity, while cell-free extract appeared high activity of 1.45 units, clearly showing that decolorization activity was due to the cell-free extract. Comparing decolorization activities of cell fractions, it was found that decolorization activity was located at the compartment of cytoplasmic membrane. The enzyme activity was also shown to be Mg++-dependent. The optimum pH and temperature of enzyme activity were 7.0 and 50°C, respectively. The thermostability of this enzyme at 35°C was kept to 58% for 3 hours.